Development of magnetic/plasmonic nickel ferrite/gold nanoparticles covered with lipid bilayers for applications in combined cancer therapy - Rodrigues, Ana Rita Oliveira (2019)
In this work, magnetic/plasmonic nanoparticles of nickel ferrite/gold were prepared and characterized, including core/shell nanoparticles (with a nickel ferrite magnetic core and a gold plasmonic shell) and nickel ferrite nanoparticles decorated with gold nanoparticles. In order to develop applications in combined cancer therapy, the prepared nanoparticles were covered with a lipid bilayer, these systems being able to transport drugs. The heating capabilities of the nanosystems were evaluated through the fluorescence quenching of the dye rhodamine B incorporated in the lipid bilayer upon excitation with a light source. The developed multifunctional nanosystems have shown promising results for application combined cancer therapy (chemo/phototherapy).